Daily food consumption in a rural Roman villa: excavations at Lički Ribnik, Croatia - Reed, K; Roguljić, IO; Radović, S; Kolak, T (Archeologicke Centrum Olomouc, 2019)
Large volumes of work exist on Roman villas; however, what the inhabitants ate on a daily basis at these sites is frequently overlooked. Here we present archaeobotanical, zooarchaeological and pottery evidence to explore aspects of daily consumption patterns within the rural villa of Lički Ribnik, Croatia. The remains date from the second half of the 2nd to the first half of the 3rd century AD and provide the first evidence of villa consumption in the Lika region. The discovery of broomcorn millet (Panicum miliaceum) grains, domestic cattle (Bos taurus) and sheep (Ovis aries) bones suggest that they were consumed at the site. Different pottery types and fabrics also suggest a range of dishes were cooked, including the Roman dish patina. Although these conclusions are based on very limited data, the study shows the importance of looking at environmental evidence in conjunction with other archaeological material in order to explore local diet and economy in the Roman period.